Recombinant Vesicular Stomatitis Virus Vaccine Vectors Expressing Filovirus Glycoproteins Lack Neurovirulence in Nonhuman Primates - Mire, Chad E. (Public Library of Science, 2012)
The filoviruses, Marburg virus and Ebola virus, cause severe hemorrhagic fever with high mortality in humans and nonhuman primates. Among the most promising filovirus vaccines under development is a system based on recombinant vesicular stomatitis virus (rVSV) that expresses an individual filovirus glycoprotein (GP) in place of the VSV glycoprotein (G). The main concern with all replication-competent vaccines, including the rVSV filovirus GP vectors, is their safety. To address this concern, we performed a neurovirulence study using 21 cynomolgus macaques where the vaccines were administered intrathalamically. Seven animals received a rVSV vector expressing the Zaire ebolavirus (ZEBOV) GP; seven animals received a rVSV vector expressing the Lake Victoria marburgvirus (MARV) GP; three animals received rVSV-wild type (wt) vector, and four animals received vehicle control. Two of three animals given rVSV-wt showed severe neurological symptoms whereas animals receiving vehicle control, rVSV-ZEBOV-GP, or rVSV-MARV-GP did not develop these symptoms. Histological analysis revealed major lesions in neural tissues of all three rVSV-wt animals; however, no significant lesions were observed in any animals from the filovirus vaccine or vehicle control groups. These data strongly suggest that rVSV filovirus GP vaccine vectors lack the neurovirulence properties associated with the rVSV-wt parent vector and support their further development as a vaccine platform for human use.